Intellectual Capital Performance Of State-Owned Enterprises In Indonesia - Rima Rachmawati; Deliana Deliana; Rini Lestari (Kajian Akuntansi, 2022)
Tujuan penelitian ini untuk mengukur kinerja pengelolaan modal intelektual di Badan Usaha Milik Negara dengan menggunakan model Pulic dikenal dengan Value Added Intellectual Capital. Data yang digunakan adalah laporan keuangan BUMN tahun 2020. Hasil kajian menunjukkan 10 BUMN dengan kategori top performance dan 11 BUMN dengan kategori bad performance. Implikasi penilaian ini mendorong BUMN untuk terus membenah dalam memanfaatkan modal intelektual untuk menciptakan nilai agar mampu bertahan dan memiliki daya saing di Era Pengetahuan saat ini.The purpose of this study is to measure the performance of intellectual capital management in State-Owned Enterprises using the Pulic’s model known as Value Added Intellectual Capital. The data used is the financial statements of SOEs for 2020. The results of the study show 10 SOE’s in the top performance category and 11 SOE’s in the bad performance category. The implications of this assessment encourage SOE’s to continue to improve in utilizing intellectual capital to create value in order to be able to survive and have competitiveness in the current Knowledge Age.